Exploring potential causal models for climate-society-conflict interaction - Guo, Weisi; Sun, Schyler; Wilson, Alan (SciTePress - Science and Technology Publications, 2023)
Climate change affects human liveability and may increase the likelihood of armed violence. However, the precise repercussions on social cohesion and conflict are difficult to model, and several socio-economic mechanisms exist between local climate changes and conflict, and are often hidden to us. Nonetheless, we offer an exploratory data analysis in this paper at a global scale, on the relationship between diverse climate indicators and conflict. Here we investigate potential basic causal models between climate change and conflict, including the causal direction, causal lag, and causal strength. We use historical climate and extreme environmental event data from the past 50 years across the world to identify geographic region-specific causal indicators. The initial broad findings are: (1) rainfall is a reasonably general indicator of conflict, (2) there are fragile regions which exhibit a strong causal link between extreme climate variations and conflict (predominantly in Africa and South Asia), and 3. there exists a common time lag of the causality between the climate variations and the conflict in many regions, which is worth further study.
Keywords: Conflict; Climate Change; Causal Models